Sistem Diagnosa Stunting Menggunakan Teorema Bayes - Kamto, Kevin Arsan; Purnomo, Agus Sidiq (Universitas Multi Data Palembang, 2024)
Stunting is a chronic nutritional problem that impacts children's physical and cognitive growth. This research develops an expert system based on Bayes' Theorem to diagnose stunting, and utilizes artificial intelligence (AI) technology. The Bayes Theorem method is used for its ability to overcome data uncertainty and produce more accurate decisions. Data was collected through interviews with pediatricians and medical records from posyandu. The system was designed using flowcharts and DFD, then implemented and tested with samples of 30 children from the Kaligrenjeng Village Posyandu. The results of the diagnosis showed a 100% accuracy rate. Validation of the results shows the expert system according to the expert's diagnosis.